The Measurement of Perceived Job Characteristics: The Job Diagnostic Survey Versus The Job Characteristics Inventory - Pierce, Jon L.; Dunham, Randall B. (Academy of Management Journal, 1978)
The article compares the job diagnostic survey and the job characteristics inventory as a measure of perceived job characteristics. The four a priori dimensions of the job characteristics inventory are discussed. Several charts that list the intercorrelation between the job diagnostic survey and the job characteristics inventory are presented. The article also covers the investigation of the dimensionality and internal consistency of two perceptual measurers of job design. The reasons for the superiority of the job characteristics inventory are also discussed.